A study to find out the correlation between grip strength, forearm circumference, forearm length and forearm skinfold in badminton players - Dutta, P.; Shivasharanappa, K. k.; Thomas, A.; Kumar, S. S.; Jeyakumar (Journal of Pharmaceutical Negative Results, 2022)
Background: A sturdy grip is formed by the powerful flexion of all the phalanges that a person can under normal biomechanical conditions. It is a functional variable which depends on age, gender and built of a person. It is also specifying overall muscles strength of a person. Grip strength is a useful guide of nutritional status. A powerful hand grip is a key component in performance of Badminton. This study is intended to find the corelation of grip strength with other anthropometric measurements of the upper limb such as forearm circumference, forearm length, and forearm skinfold for badminton players. Method: 300 recreational badminton players were included within the age group of 18 to 38 years. Height, weight and age was documented for the participants. Grip strength was recorded using a hand-held dynamometer. Forearm length and forearm circumference was measured using a measuring tape. Forearm skin fold was measured using a skinfold calliper. Correlation was carried out for grip strength with forearm circumference, forearm length and forearm skin fold by using Pearson`s correlation. Result: Statistical Analysis was performed using SPSS 15 and the outcome was considered by keeping 0.05 level of significance. There was a highly significant correlation between grip strength, forearm circumference and forearm length. Relatively less significant was found between grip strength and forearm skin fold measurements. Conclusion: A positive highly significant correlation was found between grip strength, forearm length and forearm circumference but there was comparatively less significant correlation observed between grip strength and forearm skinfold measurements.